Magnetic fields in Proto Planetary Nebulae. Issue Volume 9:Issue S302(2013) (7th August 2014) - Sabin, L.; Zhang, Q.; Zijlstra, A. A.; Patel, N. A.; Vázquez, R.; Zauderer, B. A.; Contreras, M. E.; Guillén, P. F.
Abstract: The role of magnetic field in late type stars such as proto-planetary and planetary nebulae (PPNe/PNe), is poorly known from an observational point of view. We present submillimetric observations realized with the Submillimeter Array (SMA) which unveil the dust continuum polarization in the envelopes of two well known PPNe: CRL 618 and OH 231.8+4.2. Assuming the current grain alignment theory, we were then able to trace the geometry of the magnetic field.